Respuesta :
Answer:
BRAINLIEST PLZZZZ
Step-by-step explanation:
Also given that (x+1) is factor of given polynomial p(x).
Need to determine value of constant c.
We will be solving above problem using factor theorem.
Factor theorem says that if ( x – a) is a factor of any polynomial f(x) , then f(a) = 0.
As in our case f(x) = p(x) and factor of p(x) is (x + 1) , which can be rewritten as (x – ( -1)) , so "a" in our case is -1 .
According to factor theorem p(-1) = 0
On substituting x = -1 , in given expression of p(x) we get
Hence value of c in the given polynomial is 1
Answer:
c = - 3
Step-by-step explanation:
[tex] \because [/tex] (x+1) is a factor of the polymonial [tex] p(x)=5x^4+7x^3-2x^2-3x+c[/tex]
Let (x + 1) =0[tex] \implies [/tex] x = - 1
[tex] \therefore [/tex] at x = - 1, p(x) =0.
[tex]p(x)=5x^4+7x^3-2x^2-3x+c \\ \\ 0 = 5( { - 1})^{4} + 7( { - 1})^{3} - 2( { - 1})^{2} - 3( - 1) + c \\ \\ 0 = 5 \times 1 + 7( - 1) - 2 \times 1 + 3 + c \\ \\ 0 = 5 - 7 - 2 + 3 + c \\ \\ 0 = 7 - 7 + 3 + c \\ \\ 0 = 3 + c \\ \\ c = - 3[/tex]